Gα(q/11) signaling tonically modulates nociceptor function and contributes to activity-dependent sensitization - Tappe-Theodor, Anke; Agarwal, Nitin; Kuner, Rohini; Lepcynzsky, Peter; Wirotanseng, Richard I.; Kurejova, Martina; Wettschureck, Nina; Offermanns, Stefan (Pain, 2012)
Peripheral injury or inflammation leads to a release of mediators capable of binding to a variety of ion channels and receptors. Among these are the 7-transmembrane receptors (G protein-coupled receptors) coupling to G(s), G(i/o), G₁₂/₁₃, or G(q/11) G proteins. Each of the G protein-coupled receptor pathways is involved in nociceptive modulation and pain processing, but the relative contribution of individual signaling pathways in vivo has not yet been worked out. The G(q)/G₁₁ signaling branch is of particular interest because it leads to the activation of phospholipase C-β, protein kinase C, the release of calcium from intracellular stores, and it modulates extracellular regulated kinases. To investigate the contribution of the entire G(q/11)-signaling pathway in nociceptors towards regulation of pain, we generated double-deficient mice lacking G(q/11) selectively in nociceptors using a conditional gene-targeting approach. We observed that nociceptor-specific loss of G(q) and G₁₁ results in reduced pain hypersensitivity following paw inflammation or spared nerve injury. Surprisingly, our behavioral and electrophysiological experiments also indicated defects in basal mechanical sensitivity in G(q/11) mutant mice, suggesting a novel function for G(q/11) in tonic modulation of acute nociception. Patch-clamp recordings revealed changes in voltage-dependent tetrodotoxin-resistant and tetrodotoxin-sensitive sodium channels in nociceptors upon a loss of G(q/11), whereas potassium currents remained unchanged. Our results indicate that the functional role of the G(q)/G₁₁ branch of G-protein signaling in nociceptors in vivo not only spans sensitization mechanisms in pathological pain states, but is also operational in tonic modulation of basal nociception and acute pain.